Adipose mesenchymal stem cells in ankle osteoarthritis: a case report - Ranzoni, Lucas Verissimo; Butturi Varone, Bruno; Ortolani, Carla Calviente; Barban Sposeto, Rafael; Kawamura Demange, Marco; Santos, Alexandre Leme Godoy (Journal of the Foot & Ankle, 2025)
Ankle osteoarthritis, mostly of traumatic origin, compromises the mobility and quality of life of patients. Conventional treatment includes physical therapy and infiltrations, while advanced cases require arthrodesis or arthroplasty. In this context, mesenchymal cells from adipose tissue emerge as a promising alternative. We report the case of a 43-year-old patient with advanced ankle osteoarthritis treated with micro-fragmented adipose tissue (MFAT) infiltration using Lipogems® technology. The procedure resulted in significant improvement in pain and joint function in the first three months, followed by partial regression at six months. The findings corroborate previous studies, suggesting transient efficacy and indicating that more advanced cases may have a limited response. Further research with larger samples and longer follow-up is needed to elucidate the therapeutic potential of this approach. Level of evidence V; Case report.